Influence of Modernity on Society in Developing Countries: Case Study: The Influence of Technopreneurship on Public Employment Policy - 'Adlan, Arief Al Hazmi (Journal of Modern Islamic Studies and Civilization, 2024)
Modernity is a "model" it cannot take and guarantee the value of previous "models" it must build its own norms, this is what makes the entry of technopreunership an interesting study to discuss, Technopreneurship is a part of technology that seeks to increase the ability of science and technology in a process in economic development and an individual business, the development of technology and purchasing power is a source of new social problems for the economy in Indonesia, although initially technopreuneurship was a solution to social problems, this happened because of the low purchasing power and knowledge that occurred in developing countries, The current era of digitalization is a product born of post modernism where postmodernists are young conservatives who along with two other groups "Old Conservatives" and "New Conservatives" are considered to be struggling to undermine the ideals of enlightenment, Technopreunership will become Public Values in explaining future events and what will be faced, Basically, the future is a world of competition between Humans and Technology, which makes a new path for Education and Policy Makers to pay more attention to equal thinking and make a breakthrough in Centric Urbanization and carry out its essence well.